Vitamin D Counteracts Mycobacterium tuberculosis-Induced Cathelicidin Downregulation in Dendritic Cells and Allows Th1 Differentiation and IFNγ Secretion - Rode, Anna K. O.; Kongsbak, Martin; Hansen, Marie M.; Lopez, Daniel Villalba; Levring, Trine B.; Woetmann, Anders; Ødum, Niels; Bonefeld, Charlotte M.; Geisler, Carsten (Frontiers in Immunology, 2017)
Tuberculosis presents a serious health problem with approximately one-third of the world’s population infected with Mycobacterium tuberculosis in a latent state. Experience from the pre-antibiotic era and more recent clinical studies have established a beneficial role of sunlight and vitamin D in patients with tuberculosis. At the same time, experimental data have shown that Th1 cells through production of IFNγ are crucial for cathelicidin release by macrophages, bacterial killing, and containment of M. tuberculosis in granulomas. Paradoxically, vitamin D has repeatedly been ascribed an immune-suppressive function inhibiting Th1 differentiation and production of IFNγ in T cells. The aim of this study was to investigate this apparent paradox. We studied naïve human CD4+ T cells activated either with CD3 and CD28 antibodies or with allogeneic dendritic cells (DC) stimulated with heat-killed M. tuberculosis (HKMT) or purified toll-like receptor (TLR) ligands. We show that vitamin D does not block differentiation of human CD4+ T cells to Th1 cells and that IL-12 partially counteracts vitamin D-mediated inhibition of IFNγ production promoting production of equal amounts of IFNγ in Th1 cells in the presence of vitamin D as in T cells activated in the absence of vitamin D and IL-12. Furthermore, we show that HKMT and TLR2 ligands strongly down-regulate cathelicidin expression in DC and that vitamin D counteracts this by up-regulating cathelicidin expression. In conclusion, we demonstrate that vitamin D counteracts M. tuberculosis -induced cathelicidin down-regulation and allows Th1 differentiation and IFNγ secretion